PERAN PENDIDIKAN KEPRIBADIAN DALAM MENDIDIK GENERASI MUDA DI SEKOLAH KATOLIK Studi Kasus di SMP Pangudi Luhur Sedayu Yogyakarta - Fransiskus David Ludiranto (Jurnal Teologi (Journal of Theology), 2013)
Education is one of human efforts to be a complete human. Education aims to teach young people to become homo that human, cultured human that realizes his true personality as the image of God. Therefore, education is often viewed as a part of Gods salvation. Education is a Christian journey to the fullness of human life to reach God, source and purpose of all things. Education is an appropriate way to spread Good News brought by Jesus Christ to all people. The main purpose is to educate young people to the passionate belief to Jesus Christ, the Human Salvatore because everyone who believes in him will not perish but have eternal life (John 3:16)."Education is an integral part of Gods salvation. This concept can become into reality with an effort to make a personality education as a main focus in education. Personality education teaches morality and behavior to students so that they have a good character and realize the essence of themselves as creation. The core of personality education is involving students in education. It means students have chance to have a role in the school. When the students have a role in the school, they integrate the good value in the school to themselves so that they have good characteristics. A right and good personality education will bear a good fruit that is the students will blossom appropriate to their age.